The Gospel of Thomas and Christian origins : essays on the Fifth Gospel - Patterson, Stephen J., 1957- (Nag Hammadi and Manichaean Studies, 2013)
The essays collected in The Gospel of Thomas and Christian Origins offer a series new chapters in the history of Christianity's first century. Stephen J. Patterson, whose work on the Gospel of Thomas has circulated widely for more than two decades, argues that taking this new source seriously will require rethinking a number of basic issues, including the assumed apocalyptic origins of early Christian faith, the supposed centrality of Jesus' death and resurrection, and the role of Platonism in formulation of both orthodox and heterodox Christian theology.